Mobile Phone Flashlight‐Excited Red Afterglow Bioimaging. Issue 18 (25th March 2022) - Fan, Yuanyuan; Liu, Siwei; Wu, Min; Xiao, Leyi; Fan, Yunhao; Han, Mengmeng; Chang, Kai; Zhang, Yufeng; Zhen, Xu; Li, Qianqian; Li, Zhen
Abstract: Organic room temperature phosphorescence (RTP) materials with ultralong lifetime possess the remarkable advantage in bioimaging for elimination of background noise by characteristic time scale. However, most of RTP luminogens need to be excited by the harmful ultraviolet (UV) lamp, and exhibit green or yellow emission with shallow tissue penetration, constraining the in vivo bioimaging for further application in clinical diagnosis and pathological study. In this text, the much safer excitation process by sunlight and mobile phone flashlight is realized by organic luminogens with various electronic pull–push systems. Moreover, the bright red RTP emission with lifetime up to 344 ms is achieved by optimizing molecular geometry and electronic property. Especially, the mobile phone flashlight‐excited red afterglow imaging of lymph nodes in living mice has been realized for the first time, affording a safe and conventional approach to achieve the afterglow imaging of living mice with deep issue penetration and high signal‐to‐noise ratios. Abstract : Through the rational design of organic luminogens with strong intramolecular charge transfer and optimized molecular geometry, the mobile phone flashlight‐excited red afterglow imaging of lymph nodes in living mice is realized for the first time, offering a safe and conventional approach to realize the afterglow imaging of living mice with deep issue penetration and high signal‐to‐noise ratio.